Peran Serta Badan Pengelola Perbatasan Provinsi NTT Dalam Penyelesaian Permasalahan Batas Wilayah Darat Indonesia Dan Timor Leste - Roy Adrian Dimoe; Dhesy A. Kase; Elisabeth N. S. B. Tukan (LPPM Universitas Sains dan Teknologi Komputer, 2023)
Development and population growth during this period of modernisation have forced nations to work together to advance their own interests. Cooperating countries such as Indonesia and Timor Leste have problems related to border areas. The purpose of this research is to analyse the role of the NTT Provincial Border Management Agency in resolving land boundary issues between Indonesia and Timor Leste. This research is empirical legal research, namely research conducted by examining secondary data initially and then continuing with research on primary data in the field or on the community in accordance with the problems and objectives of the research. The results of this research show that the role of the Border Management Agency is very important in maintaining security and order in the border area, as well as facilitating cross-border trade and activities. The Border Management Agency also has a role in maintaining state sovereignty, preventing the entry of illegal goods, and monitoring the movements of people entering and leaving the border area. In addition to carrying out the coordination function, the Border Management Agency also has the function of implementing the development, management and utilisation of State Territorial Boundaries and Border Areas. It can be concluded that the role of the Border Management Agency is very important in maintaining security and order in border areas, as well as facilitating cross-border trade and activities. BPP is also expected to improve cooperative relations, use of technology, build the quality of human resources, as well as transparency and accountability in the implementation of its functions